Chemo- immunotherapy and radiation in locally advanced head and neck cancer: Where do we stand?. (April 2022) - Belgioia, L.; Becherini, C.; Bacigalupo, A.; Bonomo, P.
Highlights: Concomitant radio-chemotherapy remain the standard of care in locally advanced HNSCC. Immunotherapy leads to better oncological results in R/M HNSCC. Immunotherapy in first line treatment failed to improve outcomes. Design of trials should be based on patients selection or predictive biomarkers. Abstract: Immunotherapy represents an effective therapeutic option in the management of recurrent/metastatic head and neck squamous cell carcinoma, along with chemotherapy in metastatic disease or radiotherapy/re-irradiation for (locoregionally confined) recurrent disease. On the other hand, concomitant chemo-radiation remains the primary treatment modality in many patients with locally advanced disease. In spite of promising preclinical, it is difficult to clearly establish the role of immunotherapy in the upfront management of locally advanced head and neck squamous cell carcinoma and its integration with the standard of care. In this paper, we discuss/review the main results thus far available and outline some unanswered questions that might help design future clinical trials.